Hubungan Pendidikan, Pengetahuan Dan Budaya Terhadap Pemberian Makanan Pendamping Asi Dini Di Puskesmas Ciruas Kabupaten Serang Tahun 2019 - susanti widiasdtuti widiastuti; Marini Marini; Anggi Yanuar (JOURNAL EDUCATIONAL OF NURSING(JEN), 2020)
Impacts given MP-ASI earlier include such as the difficulty of properly digested food, greater chance of illness because the baby's immune system is not yet perfect, experiencing food allergies, having the opportunity to experience obesity. The working area of the Ciruas District Health Center in Serang District has the lowest exclusive breastfeeding coverage of 23.6%. This study aims to determine the relationship of education, knowledge and culture of breastfeeding mothers to complementary feeding of early breastfeeding at Ciruas Health Center in Serang Regency in 2019. The study used a cross sectional approach. Samples were obtained by 77 respondents. The analysis uses univariate and bivariate analysis to determine the relationship between the variables studied. The results showed that mothers who gave early breastfeeding MP were 48 people (62.3%), mothers with low education were 49 people (63.6%), less knowledge was 53 people (68.8%), and the culture of giving MP Early breastfeeding with a culture of 40 people (51.9%). There is a significant relationship between education with early breastfeeding MP (p-value = 0.014), there is a significant relationship between knowledge and early breastfeeding (p-value = 0,000) and there is a significant relationship between culture and early breastfeeding MP 0.001). There is a significant relationship between education, knowledge and culture on the provision of early breastfeeding MP. The puskesmas can be more informed and provide counseling to the public so as not to give ASI early.